The Hepatotoxicity and Adherence Advantage of Short-Course Rifapentine/Isoniazid (3HP) over Stratified Isoniazid Monotherapy (6H/9H): A Systematic Review and Meta-Analysis - Agus Subhan; Rohani Lasmaria (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: The global strategy to eliminate tuberculosis hinges critically on neutralizing the latent reservoir. For decades, the standard of care has been daily Isoniazid monotherapy for 6 or 9 months. However, the effectiveness of this regimen is historically compromised by poor adherence due to its duration and significant rates of hepatotoxicity, particularly in older adults. The 3-month once-weekly regimen of Rifapentine plus Isoniazid offers a promising alternative, yet a consolidated high-level analysis comparing it specifically against stratified Isoniazid monotherapy across diverse high-risk groups was necessary to justify global policy shifts. Methods: We conducted a systematic review and meta-analysis of eight pivotal studies, including large-scale randomized controlled trials and programmatic surveillance studies. Outcomes included prevention of active tuberculosis, Grade 3/4 hepatotoxicity, and treatment completion. Data were pooled using a random effects model to account for clinical heterogeneity. Subgroup analyses stratified comparators by duration and administration method. Results: The analysis of over 10,000 participants revealed that the short-course regimen was non-inferior to isoniazid monotherapy for tuberculosis prevention (Pooled Risk Ratio 0.54; 95% CI 0.30–0.97). Crucially, the Rifapentine-based regimen demonstrated a profound reduction in grade 3/4 hepatotoxicity compared to Isoniazid monotherapy (Pooled Risk Ratio 0.16; 95% CI 0.08–0.32), with the benefit most pronounced in elderly populations. Treatment completion was significantly higher in the short-course group (Pooled Risk Ratio 1.25; 95% CI 1.15–1.36), with programmatic data confirming adherence exceeding 85% even under self-administration. Conclusion: The 3-month Rifapentine/Isoniazid regimen offers a superior safety profile and significantly higher treatment completion rates compared to Isoniazid monotherapy while maintaining equivalent efficacy. The regimen’s ability to minimize liver injury while maximizing adherence supports its adoption as a preferred standard of care, particularly for older adults.